(untitled) (Acta Scientiarum. Biological Sciences, 2022)
Species Cichla piquiti and Cichla kelberi are found in the Serra da Mesa reservoir, Goiás and are sedentary with diurnal habits. This study aimed to evaluate the magnitude and distribution of genetic variability in subpopulations of C. piquiti with specific microsatellite loci and to test transferability in other microsatellite markers for C. kelberi. We analyzed 99 individuals of C. piquiti from seven points to evaluate genetic diversity and structure with 10 microsatellite loci. Transferability of 75 loci was tested in C. kelberi to increase microsatellite markers available. Genetic structure was assessed with Bayesian clustering. Global FST for C. piquiti was weak (0.056), but FIS (0.598) and FIT (0.621) were significantly high, indicating that the mating system has a strong influence on the organization of genetic variability with most mating among related. Two genetic groups were evidenced with most individuals allocated to a single group. Transferability of microsatellite loci for C. kelberi had low polymorphism. The level of genetic diversity was low, increasing inbreeding and suggesting that few individuals of C. piquiti colonized the reservoir during its installation due founder effect. Other factors as reproductive behavior and overfishing can act to decrease genetic diversity. Therefore, we reinforce the need for genetic monitoring to avoid loss of genetic diversity that can be intensified both construction of hydropower plants and ecological and reproductive aspects in some fish species.